Advancements in Molecular Medicine and Tailor-Made Therapeutics - Rehan Imad; Talat Mirza (ziauddin University, 2024)
The marvelous success in the field of molecular therapeutics is being witnessed by science over the past few decades. From single cell RNA sequencing to circulating cell free DNA detection in the blood, astonishing accomplishments have been achieved. These advancements, however, are still confronting the challenges of the old times, such as non-specificity, inter-individual variability, and off-target effects. Molecular medicine as a science has provided a platform to address these problems, by tailoring according to the molecular and genetic profile of the individuals to increase the specificity of the treatment, to reduce variability, and to minimize adverse side effects.